A study on the phytoplankton community structure in the Diaohe River section of the Middle Route of the South-to-North Water Diversion Project in winter - Yi Xu (IWA Publishing, 2021)
As the first span and aqueduct of the Middle Route of the South-to-North Water Diversion Project, Diaohe Aqueduct has brought good engineering and social benefits since its completion. In order to understand the present water quality of the Diaohe River section of the route, four samplings were conducted at Diaohe Aqueduct in the winter of 2018. The main results of this study are as follows: 62 species (or variants) of phytoplankton belonging to 32 genera, 22 families and six phyla were identified during the study period, among which Bacillariophyta are the most dominant species. The identified phytoplankton fall into eight indicator grades: os; ps, αm; ps, αm, βm; αm; αm, βm; αm, βm, os; βm; and βm, os. A total of 17 functional groups are detected, among which TB is the absolute dominant functional group. Based on the composition characteristics of phytoplankton, the water quality trophic state of Diaohe Aqueduct is mesotrophic. However, other physical indexes show that the water quality of the Middle Route of the South-to-North Water Diversion Project is good. The conclusions drawn using phytoplankton alone as the evaluation index may not be comprehensive. In future research, how to build a comprehensive index system combining other water quality indexes for the Middle Route of the South-to-North Water Diversion Project needs yet to be improved and tested. HIGHLIGHTS Sixty-two species of phytoplankton were measured in Diaohe Aqueduct of MPR in winter.; A diatom, such as Fragilaria, Cymbella, was the main dominant species.; TB functional group is the absolute dominant functional group.; The water quality trophic state of the Diaohe Aqueduct is mesotrophic.; The water quality in the Diaohe Aqueduct during the study period is clean.;